Clinical Results of Comprehensive Medication Management Services in Primary Care in Belo Horizonte - Carina de Morais Neves; Mariana Martins Gonzaga do Nascimento; Daniela Álvares Machado Silva; Djenane Ramalho-de-Oliveira (Pharmacy, 2019)
The high prevalence of chronic diseases and use of multiple medications identified in Primary Health Care (PHC) suggest the need for the implementation of Comprehensive Medication Management (CMM) services. This study aimed to evaluate the clinical results of CMM services in a Brazilian PHC setting. A quasi-experimental study was performed with patients followed-up for two years (n = 90). Factors associated with the detection of four drug therapy problems (DTP) or more in the initial assessment were evaluated (univariate and multivariate analyses), as well as the clinical impact observed in laboratory parameters (HbA1c, Blood Pressure, LDL- and HDL-covariance analysis). A predominance of women (61.1%), a mean age of 65.5 years, and a prevalence of polypharmacy (87.8%)—use of five or more drugs—were observed. A total of 441 DTP was identified, 252 required interventions with the prescriber, 67.9% of which were accepted and 59.6% were solved. The main DTP were ‘non-adherence’ (28.1%), ‘need for additional drug therapy’ (21.8%), and ‘low dose’ (19.5%). Hypertension was positively associated with the identification of four DTP or more. A statistically significant reduction was detected in all assessed laboratory parameters (p < 0.05). CMM services contributed to the resolution of DTP and improved clinical outcomes.